Downregulation of VRK1 Inhibits Progression of Lung Squamous Cell Carcinoma through DNA Damage - Ning Du; Boxiang Zhang; Yunfeng Zhang (Canadian Respiratory Journal)
Background. Lung squamous cell carcinoma (LUSC) is a common malignancy. And the antitumor effect of bovine pox virus-associated kinase 1 (VRK1) is becoming a hot research topic. Methods. VRK1 expression and prognosis in LUSC were analyzed using the GEPIA database. The expression of VRK1 mRNA was detected in 25 LUSC clinical tissue samples by RT-PCR. VRK1 shRNA was transfected into LUSC NCI-H520 and SK-MES-1 cell lines to interfere with VRK1 expression, and the efficiency of VRK1 shRNA interference was detected by the western blot. The effects of VRK1 downregulation on LUSC cell viability, migration, cell cycle, and apoptosis were analyzed by the CCK8 assay, scratch assay, transwell assay, and flow cytometry. The effect of VRK1 downregulation on DNA damage response (DDR) was examined by immunofluorescence staining and western blot assays and further validated by in vivo experiments. Results. VRK1 was highly expressed in both LUSC tissues and cells. Survival analysis showed that the overall survival of LUSC patients with high VRK1 expression was significantly lower than that of LUSC patients with low VRK1 expression (P=0.0026). The expression level of the VRK1 gene was significantly higher in cancer tissues of LUSC patients than in paracancerous tissues. After transfection of VRK1 shRNA in both LUSC cells, cell activity decreased (P<0.001), migration ability started to be inhibited (P<0.001), the ratio of G0/G1 phase cells increased (P<0.001), and apoptosis rate increased (P<0.001). Immunofluorescence and western blot results showed that shVRK1 increased the level of γ-H2A.X (P<0.001) and promoted apoptosis of tumor cells (P<0.001). In addition, the results of animal experiments showed that shVRK1 had antitumor effects (P<0.001) and a combined effect with DOX (P<0.001). Conclusion. The downregulation of VRK1 significantly affected the proliferation, apoptosis, migration, and cell cycle progression of LUSC cells via DDR, suggesting that VRK1 is a suitable target for potential LUSC therapy.